APLIKASI PEMBELAJARAN IQRO BERBASIS MULTIMEDIA - Ahmad Fajar Sidiq; Nasirudin Nasirudin; Bambang Subana; Rizky Sitomo; Mohamad Fachri (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
Information lovers are truly pampered by the advancement of ever-more-modern information technology. Because of this, people appear to be inseparable from time and space. As technology advances, people are capable of producing a variety of tools and equipment to boost productivity by carrying out different tasks. A formula is created so that teachers can deliver instruction using suitable ways because the efforts made by teachers to enhance Qur'anic reading and writing are not at their best. more diversified based on the child's aptitudes in order to strengthen the Qur'anic reading and writing skills at TPQ. A system development methodology, such as the System Develop Life Cycle (SDLC) with the waterfall model, is required based on the current constraints. The classic life cycle, which describes a methodical and methodical approach to software development, starting with the user requirements specification and progressing through the planning, modelling, building, and deployment phases before ending with support for the complete project. In addition to making it easier for teachers to instruct pupils, the multimedia-based Iqro learning application was developed to assist users in learning correct and proper iqra' and makharijul letters.